ANALISIS PENGARUH CAR, NPL, NIM, BOPO, LDR TERHADAP ROA (Studi Pada Bank Pembangunan Daerah Di Indonesia Periode 2015-2018) - Adhista Setyarini (RESEARCH FAIR UNISRI, 2020)
This research is performed on order to test the influence of the variable Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Net Interest Margin (NIM), Biaya Operasional/Pendapatan Operasional (BOPO), Loan to Deposit Ratio (LDR) toward Return On Asset (ROA).Methodology research as the sample used purposive sampling, sample was accrued 26 Bank Pembangunan Daerah in Indonesia. Data analysis with multi linear regression of ordinary least square and hypotheses test used t-statistic and F-statistic at level of significance 5%, a classic assumption examination which consist of data normality test, multicolinearity test, hetersoskedasticity test and autocorrelation test is also being done to test the hypotheses.During research period show as variabel and data research was normal distributed. Based on test, multicolinearity test, hetersoskedasticity test and autocorrelation test classic assumption deviation has no founded, this indicate that the available data has fulfill the condition to use multi linear regression model. This result of research show that variable NPL did not influence ROA. Variable CAR, NIM, and LDR positive significant influence toward ROA. Variable BOPO negative significant influence toward ROA. Prediction capability from these five variable toward ROA is 63,6% where the balance 36,4% is affected to other factor which was not to be entered to research model.Key Words : Return On Asset (ROA), Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Net Interest Margin (NIM), Biaya Operasional/Pendapatan Operasional (BOPO), Loan to Deposit Ratio (LDR).